On the pitting corrosion of 2205 duplex stainless steel produced by laser powder bed fusion additive manufacturing in the as-built and post-processed conditions. (15th December 2021) - Haghdadi, Nima; Laleh, Majid; Chen, Hansheng; Chen, Zibin; Ledermueller, Carina; Liao, Xiaozhou; Ringer, Simon; Primig, Sophie
Graphical abstract: Highlights: 2205 DSS shows similar pitting potentials and passive current densities at RT irrespective of processing route. Cr is depleted adjacent to intergranular Cr2 N particles but remains above the critical value for passivation. As-built LPBF 2205 DSS shows a lower CPT compared to its hot-rolled counterpart. Post-AM heat treatment enhances the critical pitting temperature to the level of the hot-rolled DSS. Abstract: The effects of additive manufacturing (AM) and post-AM heat treatment on microstructural characteristics and pitting corrosion of 2205 duplex stainless steel were studied and benchmarked against its conventionally hot-rolled counterpart. The rapid solidification and possible loss of N associated with AM resulted in a non-equilibrium microstructure dominated by δ-ferrite with a minor fraction of austenite and abundant Cr2 N precipitation. Atom probe tomography revealed that no depletion of Cr occurs around intragranular Cr2 N. A deduction in Cr was observed adjacent to intergranular Cr2 N particles, however, Cr content in these regions remained above the critical value of 13 wt%. Post-AM heat treatment was effective in restoring the duplex microstructure while dissolving the Cr2 N precipitates. Although the pitting resistance in the as-built AM specimen was lower than that of its hot-rolled counterpart, it was fully recovered after post-AM heat treatment.